Epigenome-based cancer risk prediction: rationale, opportunities and challenges - Widschwendter, Martin; Jones, Allison; Evans, Iona; Reisel, Daniel; Dillner, Joakim; Sundström, Karin; Steyerberg, Ewout W; Vergouwe, Yvonne; Wegwarth, Odette; Rebitschek, Felix G; Siebert, Uwe; Sroczynski, Gaby; et al. (Nature reviews. Clinical oncology, 2018)
The incidence of cancer is continuing to rise and risk-tailored early diagnostic and/or primary prevention strategies are urgently required. The ideal risk-predictive test should: integrate the effects of both genetic and nongenetic factors and aim to capture these effects using an approach that is both biologically stable and technically reproducible; derive a score from easily accessible biological samples that acts as a surrogate for the organ in question; and enable the effectiveness of risk-reducing measures to be monitored. Substantial evidence has accumulated suggesting that the epigenome and, in particular, DNA methylation-based tests meet all of these requirements. However, the development and implementation of DNA methylation-based risk-prediction tests poses considerable challenges. In particular, the cell type specificity of DNA methylation and the extensive cellular heterogeneity of the easily accessible surrogate cells that might contain information relevant to less accessible tissues necessitates the use of novel methods in order to account for these confounding issues. Furthermore, the engagement of the scientific community with health-care professionals, policymakers and the public is required in order to identify and address the organizational, ethical, legal, social and economic challenges associated with the routine use of epigenetic testing.
Keywords: epigenomika; DNA Methylation; Neoplasms; Risk Assessment; rizikové faktory; genom lidský; hodnocení rizik; Humans; metylace DNA; Genome, Human; Epigenomics; Risk Factors; nádory; lidé